Effect of Dimensions of Service Quality on Satisfaction of BPJS Patiests in Outpatient Health Center Bungah Gresik Installation - Awwarij, Sakhowi A. Al; Zahroh, Chilyatiz; Wijaya, Satriya; Kamida; Adriansyah, Agus Aan (International Journal of Psychosocial Rehabilitation, 2020)
Health center is the first level health facility in the community; therefore, it must pay attention to the quality of service to patients. This study aims to determine the quality of service to the satisfaction of BPJS patients in outpatient facilities at the Bungah Gresik Health Center. Variables in this study are dimensions of service quality with patient satisfaction. The type of research used is quantitative analytical descriptive handled in February-April 2019 with a sample of 89 respondents. Data obtained through questionnaires and interviews, data analysis using a binary logistic regression statistical test. The results showed that 88.76% of respondents stated that the service quality of the Bungah health center was good and 77.53% of respondents said they were satisfied with the services of the Bungah health center. The results of statistical tests show there are influences between the dimensions of tangible, empathetic, and assurance of patient satisfaction with p-values of 0.022, 0.029, and 0.040. While the dimensions of reliability and responsiveness have no ef ect on patient satisfaction with a p-value of 0.389, and 0.316. Suggestions for Bungah health centers need to improve the quality of services by adding supporting facilities, human resources, and attention to patient complaints to improve patients’ pain.